2022
DOI: 10.1073/pnas.2104718119
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63-Senataxin circuit controls keratinocyte differentiation by promoting the transcriptional termination of epidermal genes

Abstract: Significance ΔNp63 is a master regulator of skin homeostasis since it finely controls keratinocyte differentiation and proliferation. Here, we provide cellular and molecular evidence demonstrating the functional role of a ΔNp63 interactor, the R-loop–resolving enzyme Senataxin (SETX), in fine-tuning keratinocyte differentiation. We found that SETX physically binds the p63 DNA–binding motif present in two early epidermal differentiation genes, Keratin 1 (KRT1) and ZNF750, facilitating R-loop removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…This has led many authors to propose that SETX directly resolves R-loops by unwinding the RNA:DNA hybrid portion of R-loops, therefore promoting the restoration of the natural double-stranded DNA. However, transcription, which is the major source of R-loops, is also substantially altered by SETX depletion (6062, 72). A couple of recent studies have shown that the perturbations of RNAPII genomic distribution provoked by SETX deletion/depletion are rather associated with R-loop losses at many loci (81, 82).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led many authors to propose that SETX directly resolves R-loops by unwinding the RNA:DNA hybrid portion of R-loops, therefore promoting the restoration of the natural double-stranded DNA. However, transcription, which is the major source of R-loops, is also substantially altered by SETX depletion (6062, 72). A couple of recent studies have shown that the perturbations of RNAPII genomic distribution provoked by SETX deletion/depletion are rather associated with R-loop losses at many loci (81, 82).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains possible that SETX rather controls R-loop formation by acting on RNAPII genomic occupancy. Indeed, SETX has been implicated in RNAPII transcription termination (38,(60)(61)(62) although it is unclear whether SETX has retained the ability of its yeast orthologue to induce termination or whether it rather plays an accessory role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…CKs are a heterogeneous group of proteins that contribute to the structure of intermediate filament that function as the supporting cytoskeleton in the epithelial cells [ 15 ]. The type I CKs consist of acidic proteins, arranged in pairs of heterotypic keratin chains, and the type II are basic or neutral proteins which are arranged in pairs of heterotypic keratin chains co-expressed during differentiation of simple and stratified epithelial tissues [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both ΔNp63 and SETX physically bind the p63 DNA-binding motif present in early epidermal differentiation genes, in order to facilitate R-loop removal and allow efficient transcriptional termination. Interestingly, SETX expression is deregulated in cutaneous SCC, indicating that ΔNp63 and SETX interaction is important in skin pathologies [ 96 ]. To sustain proliferation and wound repair in keratinocytes, ΔNp63 interacts with nuclear factor erythroid 2-related factor 2 (NFE2L2; NRF2).…”
Section: Exploiting the P63 Interactome In Epithelial Development And...mentioning
confidence: 99%